2019
DOI: 10.1029/2019jb017785
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Velocity Structure of the Magnetic Quiet Zone and Continent‐Ocean Boundary in the Northeastern South China Sea

Abstract: In 2016, we carried out a coincidental multichannel reflection seismic and wide-angle reflection/refraction seismic experiment along a 320-km-long profile across the northeastern margin of the South China Sea. Based on these new data, we studied velocity structure of the transitional continental crust using both forward modeling and travel-time tomography. The velocity model shows that Mesozoic sediments have velocities of 4.3-5.3 km/s and are about 3-6 km thick in the magnetically quiet Chaoshan Depression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 72 publications
(169 reference statements)
0
12
1
Order By: Relevance
“…If so, it would have cooled rapidly, making it hard to retain low-velocity in the long term. Yet, the cooled magma would have generated a high-velocity zone which, however, has not been resolved in our case nor in other reports [18]. Though not improbably, it is less likely an active magma chamber.…”
Section: Analysis Of the Hill H110 And The Low-velocity Zonecontrasting
confidence: 60%
See 2 more Smart Citations
“…If so, it would have cooled rapidly, making it hard to retain low-velocity in the long term. Yet, the cooled magma would have generated a high-velocity zone which, however, has not been resolved in our case nor in other reports [18]. Though not improbably, it is less likely an active magma chamber.…”
Section: Analysis Of the Hill H110 And The Low-velocity Zonecontrasting
confidence: 60%
“…On the whole, the northern margin of South China Sea is magma-poor, but there are enhanced young magmatism locally, particularly around the southern CSD, in expressions of volcanoes, shallow intrusive, and lower crust underplating, featuring high-velocity (7.0-7.5 km/s) [13,17,18]. However, the impact of magmatism on the petroleum system in the CSD is less known.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was not revealed in the northwestern margin (Huang, Qiu, Pichot et al., 2019; Huang et al., 2021; Qiu et al., 2001), which makes the situation of magmatism still enigmatic. In the COT, except for one wide‐angle seismic study in the northeastern margin which reveals possible exhumed mantle (Wan et al., 2019), most of the seismic and drilling data indicate a rapid transition (Larsen et al., 2018; Li, Huang, Grevemeyer et al., 2021). In the oceanic basin, the Northwest Sub‐basin and East Sub‐basin mainly show typical oceanic crust, but whether the Southwest Sub‐basin shows typical or thinned oceanic crust with serpentinized mantle is still a matter of debate (e.g., Li, Huang, Grevemeyer et al., 2021).…”
Section: Geological Settingmentioning
confidence: 99%
“…At the SCS passive margin, the role of magmatism in the processes of rifting and seafloor spreading is still a matter of debate. MCS and OBS data were used to infer a mantle exhumation model for the COT (Franke et al, 2014;Wan et al, 2019), while the IODP drilling results yielded a rapid transition from continental crust to seafloor spreading and characterized it as an intermediate-type rifted margin (Larsen et al, 2018). Spatial and temporal variations of the magmatic budget in the SCS basin (Yu et al, 2018(Yu et al, , 2021 demonstrated the unstable magmatic supply, especially before and after the ridge jump events, leading the architecture of COT in the SCS becomes an open problem and need more evidence.…”
mentioning
confidence: 99%